GURGA CHIYA AND TEPE MARANI: NEW EXCAVATIONS IN THE SHAHRIZOR PLAIN, IRAQI KURDISTAN1. (3rd November 2016) - Wengrow, David; Carter, Robert; Brereton, Gareth; Shepperson, Mary; Hamarashi, Sami Jamil; Saber, Saber Ahmed; Bevan, Andrew; Fuller, Dorian; Himmelman, Helen; Sosnowska, Hanna; Carretero, Lara Gonzalez
Abstract : Gurga Chiya and Tepe Marani are small, adjacent mounds located close to the town of Halabja in the southern part of the Shahrizor Plain, one of the most fertile regions of Iraqi Kurdistan. Survey and excavation at these previously unexplored sites is beginning to produce evidence for human settlement spanning the sixth to the fourth millennia, c . 5600–3300 cal.b.c . In Mesopotamian chronology this corresponds to the Late Neolithic through to Chalcolithic periods; the Halaf, Ubaid, and Uruk phases of conventional culture history. In Iraqi Kurdistan, documentation of these periods—which witnessed many important transformations in prehistoric village life—is currently very thin. Here we offer a preliminary report on the emerging results from the Shahrizor Plain, with a particular focus on the description of material culture (ceramic and lithic assemblages), in order to establish a benchmark for further research. We also provide a detailed report on botanical remains and accompanying radiocarbon dates, which allow us to place this new evidence in a wider comparative framework. A further, brief account is given of Late Bronze Age material culture from the upper layers at Gurga Chiya. We conclude with observations on the significance of the Shahrizor Plain for wider research into the later prehistory of the Middle East, and the importance of preserving and investigating its archaeological record.